Interpretasi Struktur Bawah Permukaan Menggunakan Metode Magnetik di Sekitar Gedung Auditorium ULM Banjarbaru, Kalimantan Selatan - Safitri, Normala; Siregar, Simon Sadok; Sudarningsih, Sudarningsih; Manik, Tetti Novalina (Jurnal Natural Scientiae, 2025)
Subsurface interpretation research has been carried out using the magnetic method with the aim of knowing the value of magnetic anomalies and subsurface rock structures around the ULM Banjarbaru Auditorium Building.In this study, data was collected using the PPM G-856 tool, which performed up to 55 measurements with a 5 m spacing between points.  According to the research findings, the magnetic field anomaly values in the study area range -1252.2 nT – 1725.4 nT. The 2D modeling results show that the study area is the Dahor formation, which consists of claystone,siltstone, and rock sand. The results of measuring the susceptibility value of each rock are 0.01; 0.015 and 0.018 SI for claystone,  0.001 and 0.0011 SI for siltstone, and 0.02 SI for rock sand.